Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Berwirausaha - Salsabila Salsabila; Sasnita Sitompul; Sabrina Iiza (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Entrepreneurship among students is seen as a relevant alternative strategy in response to limited formal employment opportunities while encouraging economic independence. This study aims to analyze the factors that influence students' interest in entrepreneurship, with an emphasis on students who run dim sum businesses as a form of independent entrepreneurship. This study applies a descriptive qualitative approach with research subjects being dim sum business students selected purposively. Data were collected through semi-structured interviews and direct observation of the production process, marketing activities, and interactions with consumers. The results show that students' interest in entrepreneurship is influenced by several main factors, including economic incentives as the most dominant factor, practical experience in business management, social support, and the flexibility of the business type, which allows students to balance their academic and entrepreneurial activities. Direct involvement in business activities also contributes to increasing students' confidence and readiness in managing businesses independently. These findings confirm that practical experience and a supportive environment play an important role in fostering students' interest in entrepreneurship.